2023
DOI: 10.1108/jwam-04-2023-0031
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and sustainable growth of full-service restaurants in the global south: testing the mediating role of dynamic capabilities

Abstract: PurposeThe purpose of this study is to establish whether dynamic capabilities mediates the association between social capital and sustainable growth of full-service restaurants in Kampala, Uganda.Design/methodology/approachThis study is cross-sectional and correlational in nature. A self-administered questionnaire was used to gather data from 154 full-service restaurants in Kampala. Statistical Package for the Social Sciences (SPSS.25) and Medgraph – Excel Version were used to conduct correlation, hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…, 2023) or enhancing managerial proficiency by developing informal networks (Ekonen and Heilmann, 2021)], it is less influential (at least in overt terms). Additionally, the influence of social capital to facilitate opportunities and identify threats has also been observed in employees in Uganda (Najjinda et al. , 2023).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, 2023) or enhancing managerial proficiency by developing informal networks (Ekonen and Heilmann, 2021)], it is less influential (at least in overt terms). Additionally, the influence of social capital to facilitate opportunities and identify threats has also been observed in employees in Uganda (Najjinda et al. , 2023).…”
Section: Discussionmentioning
confidence: 97%
“…as a form of employability capital or enhancing managerial proficiency by developing informal networks (Ekonen and Heilmann, 2021)], it is less influential (at least in overt terms). Additionally, the influence of social capital to facilitate opportunities and identify threats has also been observed in employees in Uganda (Najjinda et al, 2023). However, this comes more from the opportunities to interact at work and develop networks whilst in employment rather than the need for such networks to secure employment or access promotion opportunities.…”
Section: Addressing the Research Questionmentioning
confidence: 99%
“…Furthermore, the study demonstrated that dynamic capabilities and social capital both signi cantly and favor catalyze sustainable growth (Najjinda et al, 2023). The global social capital of the top management team has a crucially favorable contribution to innovation (Zheng et al, 2019).…”
Section: Relationship Between Innovation and Social Capitalmentioning
confidence: 89%
“…That is a key contribution of our study. Extant studies on dynamic capabilities argued that resource deployment is a key enabler for developing dynamic capabilities (Teece et al, 1997;Najjinda et al, 2023)). Furthermore, our study showed that restaurants in the country could realize dynamic capability, and it helps restaurants provide more value to their customers (Najjinda et al, 2023).…”
Section: Implications For Practicementioning
confidence: 99%